Invasive, gangrenous mucormycosis of arm: A fatal opportunistic infection in a highly immunocompromised host - Vijayanth Kanagaraju; Venkatesh Kumar Narayanasamy; Sanjeev Sukumaran; Udaya Moorthy; V Shyam Sundar; S Vidhya Lakshmi (Wolters Kluwer Medknow Publications, 2019)
Opportunistic fungal infections occur predominantly in immunocompromised (IC) patients. Mucormycosis has the highest mortality among fungal infections. The organism is ubiquitous in its presence. The infection is commonly acquired by inhalation of fungal spores or by inoculation by direct trauma. Rhinocerebral and pulmonary mucormycosis present commonly with high mortality rates. Cutaneous mucormycosis (CM) is rarely reported and usually presents in two forms, superficial and disseminated. The superficial infection occurs commonly in immunocompetent hosts, and it can sometimes turn angioinvasive and become a fatal and very aggressive disseminated disease, especially in IC hosts. Coexistant risk factors increase the mortality rate. We report a case of posttraumatic, highly lethal, angioinvasive, and gangrenous type of CM of the arm in an IC patient. Diabetic ketoacidosis and cirrhosis due to chronic alcoholic liver disease were the risk factors.